PENGATURAN DAN PRINSIP TANGGUNG JAWAB PENGANGKUT TERHADAP KORBAN KECELAKAAN PESAWAT UDARA: - Rayhan Fadhillah; Bakti Yunari, Sri (Faculty of Law, Universitas Trisakti, 2023)
As an airline, Sriwijaya Air is obligated to provide the security, safety, and comfort of travelers. The aircraft being used during flying operations must be in a flyable state. near this sense, on January 9, 2021, a Sriwijaya Air airliner crashed near the Thousand Islands, killing all 62 aboard the aircraft - passengers and crew combined. Problem statement: Based on Law No. 1 of 2009 Concerning Aviation, what are the fundamentals of carrier duty for passengers in private air transport law, and how is carrier responsibility for victims in the Sriwijaya Air plane accident in the Thousand Islands regulated? descriptive normative research design employing both primary and secondary data, analyzed qualitatively and deductive methods for drawing conclusions. The results of the research and discussion show that the regulations that can be applied are Article 141 paragraph (1) of Law no. 1 concerning Aviation explains that the carrier must be responsible for losses suffered by passengers on board and/or getting on and off the aircraft and the principle of carrier responsibility that is applied is the principle of presumption of liability. Conclusion The carrier must pay for losses suffered by passengers, namely Rp. 1,250,000,000